2020
DOI: 10.1093/neuonc/noaa104
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, safety, and tolerability of olaparib and temozolomide for recurrent glioblastoma: results of the phase I OPARATIC trial

Abstract: Background The poly(ADP-ribose) polymerase (PARP) inhibitor olaparib potentiated radiation and temozolomide (TMZ) chemotherapy in preclinical glioblastoma models but brain penetration was poor. Clinically, PARP inhibitors exacerbate the hematological side effects of TMZ. The OPARATIC trial was conducted to measure penetration of recurrent glioblastoma by olaparib and assess the safety and tolerability of its combination with TMZ. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 24 publications
5
76
0
Order By: Relevance
“…Grade 3/4 myelotoxicity was observed in 20% of treated patients with a median PFS of 2 months (95% CI, 1.9–2.1) for both arms and 6m-PFS of 4.4% and 17% for bevacizumab refractory and bevacizumab naïve, respectively [ 151 ]. Another phase I trial evaluated Olaparib, an oral PARP1 and PARP2 inhibitor, in combination with temozolomide in rGBM patients [ 152 ]. Grade 3/4 myelosuppression was observed in 20% overall and the median PFS was about 2 months…”
Section: Summary Of Major Phase II Clinical Trialsmentioning
confidence: 99%
“…Grade 3/4 myelotoxicity was observed in 20% of treated patients with a median PFS of 2 months (95% CI, 1.9–2.1) for both arms and 6m-PFS of 4.4% and 17% for bevacizumab refractory and bevacizumab naïve, respectively [ 151 ]. Another phase I trial evaluated Olaparib, an oral PARP1 and PARP2 inhibitor, in combination with temozolomide in rGBM patients [ 152 ]. Grade 3/4 myelosuppression was observed in 20% overall and the median PFS was about 2 months…”
Section: Summary Of Major Phase II Clinical Trialsmentioning
confidence: 99%
“…Olaparib is undergoing a Phase-I clinical trial for GBM in combination with radiation, TMZ and bevacizumab. Despite no evidence for Olaparib as a CNS available drug, it is being tested for brain tumors as well, as recent evidence has highlighted that many GBM patients show compromised integrity of the BBB and that in such cases, Olaparib may be successfully delivered to the tumor [ 90 ].…”
Section: Inhibition Of Ddr Kinases To Overcome Therapy Resistance mentioning
confidence: 99%
“…While talazoparib, olaparib, and rucaparib show limited penetration across intact BBB as they are liable to efflux by the BBB, veliparib and niraparib were shown to have better penetration [33,34]. However, results from a Phase I clinical trial (OPARATIC trial) showed that olaparib was able to accumulate in marginal and core tumors in GBM patients who were treated with low doses of temozolomide [35].…”
Section: Tracer Modality Of Imaging Development Phasementioning
confidence: 99%